2015
DOI: 10.1007/s10072-015-2269-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone therapy and risk of recurrence/progression in intracranial tumors: a meta-analysis

Abstract: Growth hormone deficiency is common in intracranial tumors, which is usually treated with surgery and radiotherapy. A number of previous studies have investigated the relationship between the growth hormone replacement therapy (GHRT) and risk of tumor recurrence/ progression; however, the evidence remains controversial. We conducted a meta-analysis of published studies to estimate the potential relation between GHRT and intracranial tumors recurrence/progression. Three comprehensive databases, PUBMED, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Similar results were also reflected from the analysis conducted by Liang Shen et al in children with intracranial tumors, craniopharyngioma, medulloblastoma, astrocytoma, or glioma [24]. Ideally, this result should be confirmed by a large-scale multicenter prospective randomized study with sufficiently long follow-up duration.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were also reflected from the analysis conducted by Liang Shen et al in children with intracranial tumors, craniopharyngioma, medulloblastoma, astrocytoma, or glioma [24]. Ideally, this result should be confirmed by a large-scale multicenter prospective randomized study with sufficiently long follow-up duration.…”
Section: Resultssupporting
confidence: 75%
“…And another meta-analysis showed that the risk of recurrence for pediatric brain tumors was not increased in patients treated with GH [23]. Open Journal of Endocrine and Metabolic Diseases [24]. And a study of pediatric GH treatment which conducted by Child C.J et al also showed that if there has no history of malignancy, the risk of primary cancer did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the undeniable anti-apoptotic and anabolic effect of GH, the exact mechanism by which tumor cells are unprotected remains unknown; thus, the threat of increased future cancer risk or tumor recurrence, impedes its clinical use in oncological patients. However, several data from long-term patient surveillance and meta-analysis studies suggest the safety of low-dose GH treatment, concluding that GH therapy does not increase the risk of cancer (38)(39)(40). Further investigations are highly recommended to establish the clinical applicability of GH in cancer patients treated with chemotherapy and to explore the possible interference with the anti-tumor activity of cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we performed sensitivity analyses to investigate the stability of the overall estimation with respect to each study by excluding studies one by one. Additionally, Begg's and Egger's tests were adopted to assess publication bias (Shen et al., ).…”
Section: Methodsmentioning
confidence: 99%